What Do Older Adults’ Global Self-ratings of Oral Measure? - David Locker, PhD, Evelyn Wexler MScN; Aleksandra Jokovic, PhD (Blackwell Synergy, 2005)
Although global self-ratings of oral health are widely used in oraf health research, the frames of reference on which older people‘s ratings are based are not known. This study used a quantitative approach in order to identify these referents.